Labor and Government Policies on Poverty Reduction in Sumatera Island, Indonesia - Purmini Purmini; Roosemarina Anggraini Rambe (Department of Development Economics, Universitas Sriwijaya, 2021)
This study aims to analyze the effect of agricultural workers, education level, female workers and the role of government policies on poverty rate in Sumatra. Observations were made in 151 districts/cities in Sumatra during the period 2013-2015 and 2017-2018. The approach used is a panel data regression model. The method applied is random effect. The findings show the labor in the agricultural sector has a significant and positive effect on the poverty rate in Sumatra, while the level of education and government spending has a significant and negative effect on the poverty rate. The policy implication is that it is necessary to increase labor productivity in the agricultural sector and other industries that are more efficient. The government also needs to strengthen the agricultural sub-sector in order to have better value-added products. Optimizing and improving basic services such as education, health, economic and social.